Asean Economic Community 2015: Player or Spectator? - Mudrajad Kuncoro (Journal of World Trade Studies, 2010)
Basically the blueprint of AEC is to build Asean Economic Community as an integrated area for the distribution of goods, services, investment, capital, and skillful work force. 2008 is the year to start establishing the area in that 2015 is expected to be the time for the implementation. It can be said that AEC is nonetheless AFTA plus. This article analyzes the methods and steps in realizing AEC. The question is, are we ready? Will we be the player ot the spectator in AEC 2015? Perhaps the myth of united ASEAN will vanish should AEC be really established. However, there must be some barriers in the ways of establishing AEC 2015. This article identifies the obstacles in both Indonesia and in ASEAN. There is a big gap among the ten members of ASEAN. As the commitment to carry out the programs of AEC heading a competitive economic area, Indonesia has issued two outputs: first, Government Regulation on the Ratification of Protocol to Implement the Third Package of Commitments on Financial Services under the ASEAN Framework Agreement on Services (AFAS). Second, Government Regulation on the Ratification of Protocol to Implement the Fourth Package of Commitments under the ASEAN Framework Agreement on Services (AFAS).